Probabilistic Study into the Impact of Soil Spatial Variability on Soil Consolidation by Prefabricated Vertical Drains - Bari, Wasiul; Shahin, Mohamed; Nikraz, Hamid (Techno-Press, 2012)
Soil consolidation by prefabricated vertical drains (PVDs) relies on several soil properties that are spatially variable such as the coefficients of permeability and volume compressibility. However, available design methods assume a single best estimate of the degree of consolidation based on “average” soil properties that are used to define an “equivalent” homogeneous soil. For heterogeneous soils, however, this assumption can result in desired (predicted) degree of consolidation that may not be reached at the required time, leading to unreliable and uneconomical solutions. To date, a few studies have been carried out to investigate the effects of spatial variability on soil consolidation and more research is immensely needed. In this paper, the effects of spatial variability of soil permeability and volume compressibility on consolidation of soft soil by PVDs are investigated stochastically by combining the local average subdivision (LAS) method of the random field theory and the Monte-Carlo finite-element simulations. The results indicate that spatial variability of soil permeability and volume compressibility within an affected soil mass significantly affects the degree of consolidation achieved via PVDs and hence the amount of soil improvement.